African immigrants' experiences in American schools : complicating the race discourse - Mthethwa-Sommers, Shirley, 1968-; Harushimana, Immaculée, 1960- (Race and education in the twenty-first century., 2016)
This book addresses how educators create more inclusive K-12 classrooms for African-born students in American schools. The authors analyze how gender, spirituality, colonization, and religious affiliation as well as American-rooted factors complicate the integration of these students into the educational school system in the United States.